2014
DOI: 10.3892/mmr.2014.2032
|View full text |Cite
|
Sign up to set email alerts
|

Human heat shock protein 27 exacerbates ischemia reperfusion injury in rats by reducing the number of T regulatory cells

Abstract: Ischemia reperfusion injury (IRI) occurs in almost every liver surgery and is associated with the reduction of the liver blood flow. Ischemia impairs liver function and can even cause liver failure following surgery. The present study aimed to identify a new molecular target allowing the reduction of IRI and explore the related cellular mechanism. Adenovirus (~2.5x10(12) viral particles) bearing the human heat shock protein 27 (HSP27) gene was injected into rat liver through the ileocecal vein. Five days follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Ye et al. found that HSP27 accelerated the early acute liver injury induced by ischemia–reperfusion injury in rats by reducing the number of Treg cells, reducing levels of the stress-protective factors superoxide dismutase (SOD) and glutathione, increasing the level of proinflammatory factors, and aggravating inflammation ( 73 ). Wright et al.…”
Section: Types and Functions Of Damps Related To Aclfmentioning
confidence: 99%
See 1 more Smart Citation
“…Ye et al. found that HSP27 accelerated the early acute liver injury induced by ischemia–reperfusion injury in rats by reducing the number of Treg cells, reducing levels of the stress-protective factors superoxide dismutase (SOD) and glutathione, increasing the level of proinflammatory factors, and aggravating inflammation ( 73 ). Wright et al.…”
Section: Types and Functions Of Damps Related To Aclfmentioning
confidence: 99%
“…Most scholars believe that HSPs are important protective factors in the repair of liver tissue damage and that increases in their levels are helpful for the prognosis of patients and predicting efficacy, but the mechanism of some remains controversial. Ye et al found that HSP27 accelerated the early acute liver injury induced by ischemia-reperfusion injury in rats by reducing the number of Treg cells, reducing levels of the stress-protective factors superoxide dismutase (SOD) and glutathione, increasing the level of proinflammatory factors, and aggravating inflammation (73). Wright et al conducted ACLF-related animal experiments and showed increased HSP25 in the corpus callosum of the bile duct ligation (BDL) rat model, suggesting a cell stress state (such as inflammation and apoptosis) (87).…”
Section: Heat Shock Proteinsmentioning
confidence: 99%